Photosensitivity and Radiosensitivity of Methylene Blue (MB) With Gold Nanoparticles Coated By Thioglucose (Gnps-Tio): An In Vitro Study - Maryam Shabanzadeh; Zahra Mohammadi; Armin Imanparast; Ameneh Sazgarnia (Iranian Journal of Medical Physics, 2023)
Introduction: Multifunctional of cancer-specific tumor biomarkers is a potent therapeutic approach to treat cancer diseases with high efficacy. Among these methods that can be mentioned are the composition and design of nanoparticles and photosensitizers (PS). The purpose of this study is to investigate the effect of gold nanoparticles (GNPs) coated thioglucose (Tio) combined with methylene blue photosensitizer to enhance the efficacy of hybrid therapy (photodynamic and radiation therapy).Material and Methods: First, GNPs-Tio was synthesized. Next, the toxicity of GNPs-Tio, MB, and their combinations was determined on the MCF-7 cell line to achieve their optimal concentrations. In the next step, the efficacy of combination therapy was evaluated using hybrid therapy. For this purpose, an optical dose of 15.6 J/cm2 and 2 Gy for radiation therapy were delivered. Cell viability was evaluated using MTT and colony assays.Results: According to the MTT assay, the combined photodynamic and radiation treatment of GNPs-Tio did not cause significant cell death. But this induced significant cell death by using GNPs-Tio + MB while the cell survival rate was almost zero. Combined therapy caused significant cell death in the presence of each of the pharmacological agents alone and their combination in colony assay.Conclusion: The difference in treatment results between the MTT and the colony assay can be due to the more accurate colony assay for cell death detection. Significant cell death was achieved in the combination of photodynamic and radiotherapy in the presence of MB and MB + GNP-Tio.